Physical Activity Among Muslim Adolescents in Indonesia - Husna Hidayati; Urai Hatthakit; Sang-Arun Isaramalai (Idea Nursing Journal, 2018)
Purpose: To describe the physical activity among Muslim adolescents in Aceh province, Indonesia and to identify the correlates of demographic characteristics to physical activity.Methods: This study was a cross sectional study. One hundred and fifty adolescents in senior high school who met the inclusion criteria were recruited from Banda Aceh municipality and Aceh Besar district in Aceh province, Indonesia. Physical activity was analyzed using descriptive statistics.Result: The level of physical activity in Indonesian Muslim adolescents were at a moderate level. Additional analysis of several demographic characteristics revealed that gender had a significant influence on physical activity while the other variables had no statistical influence on physical activity.Conclusion: The findings of this study have provided evidence regarding the level of physical activity in Indonesian Muslim adolescents. This study can be used as baseline data for further knowledge development and studies related to this area still can be conducted for better understanding. Keyword: Adolescent, Physical Activity, Health Promotion